Techno-Sociocultural Influences on Accelerating English Learning through DGBL - Atmaja, Theodore Alexander (Universitas Tanjungpura, 2025)
This study investigates the socio-cultural influences on high school students regarding the integration of technology, specifically video games, in English language teaching (ELT). Motivated by the pervasive impact of modernization and the increasing necessity for effective English language acquisition in a globalized context, this study examines the feasibility and impact of technology application in ELT within a socio-cultural framework. Employing a quantitative case study design, the study involved 120 student participants and 16 educators utilizing interactive video game applications in conventional classroom settings, alongside questionnaires and observations for data collection. The findings indicate a strong consensus among educators regarding the significance of socio-cultural factors in ELT, although their practical integration varied considerably. Educators recognized video games as effective tools for enhancing learner motivation and language skills, a sentiment that was echoed by students. However, challenges such as technical difficulties, time constraints, and limited access to technology were prevalent. Notably, students exhibited pre-existing familiarity with video games, suggesting the potential of Digital Game-Based Learning (DGBL) to harness existing engagement. The study concludes with recommendations that emphasize the importance of purposeful game selection, scaffolding, and institutional support in addressing implementation challenges and fostering a more favorable attitude towards DGBL.